Spatially graded porous transport layers for gas evolving electrochemical energy conversion: High performance polymer electrolyte membrane electrolyzers. (15th December 2020) - Lee, Jason K.; Lee, ChungHyuk; Fahy, Kieran F.; Kim, Pascal J.; LaManna, Jacob M.; Baltic, Elias; Jacobson, David L.; Hussey, Daniel S.; Stiber, Svenja; Gago, Aldo S.; Friedrich, Kaspar A.; Bazylak, Aimy
Graphical abstract: Highlights: Low to high porosity gradient in the anode PTL for high performance. 50% reduction in PTL gas with low to high porosity gradient. Enhanced water permeability for low to high porosity gradient. Abstract: Decarbonizing society's energy infrastructure is foundational for a sustainable future and can be realized by harnessing renewable energy for clean hydrogen and on-demand power with fuel cells. Here, we elucidate how graded porous transport layers (PTLs) are instrumental for high performance gas evolving electrochemical energy conversion devices, with an emphasis on polymer electrolyte membrane (PEM) electrolyzers. Spatially graded PTLs fabricated by vacuum plasma spraying are examined via in operando neutron imaging, electrochemical characterization, and pore network modelling. The results reveal the staggering benefits of positioning the lower porosity region adjacent to the catalyst layer and the higher porosity region adjacent to the flow field, which lead to current densities up to 4.5 A/cm 2 with a 29 % reduction in cell potential, 38 % reduction in mass transport overpotential, and 50 % reduction in PTL gas saturation. The liquid water permeability of the PTL also enhances by an order of magnitude, with a drastic reduction in gas saturation adjacent to the catalyst layer. Custom graded PTLs have the potential to transform performance levels for a broad array of gas evolving electrochemical energy conversion devices.